2001
DOI: 10.1046/j.1365-8711.2001.04415.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical abundances and winds of massive stars in M31: a B-type supergiant and a WC star in OB 10

Abstract: We present high quality spectroscopic data for two massive stars in the OB 10 association of M31, OB 10‐64 (B0 Ia) and OB 10‐WR1 (WC6). Medium resolution spectra of both stars were obtained using the ISIS spectrograph on the William Herschel Telescope. This is supplemented with Hubble Space Telescope STIS UV spectroscopy and Keck I HIRES data for OB 10‐64. A non‐local thermodynamic equilibrium (LTE) model atmosphere and abundance analysis for OB 10‐64 is presented, indicating that this star has similar photosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 43 publications
6
69
0
Order By: Relevance
“…Both #29 (WC5) and #48 (WC4) lie on, or slightly below, the Galactic calibration, as would be expected from the metallicities inferred from their locations in NGC 300 (Deharveng et al 1988;Zaritsky et al 1994). Of course, the difference between Galactic and LMC calibrations amounts to less than a factor of two in mass-loss rate, and Smartt et al (2001) discuss, in detail, limitations with adopting generic H  region abundances with regard to WC properties in M 31.…”
Section: Comparison With Wc Stars In the Galaxymentioning
confidence: 74%
“…Both #29 (WC5) and #48 (WC4) lie on, or slightly below, the Galactic calibration, as would be expected from the metallicities inferred from their locations in NGC 300 (Deharveng et al 1988;Zaritsky et al 1994). Of course, the difference between Galactic and LMC calibrations amounts to less than a factor of two in mass-loss rate, and Smartt et al (2001) discuss, in detail, limitations with adopting generic H  region abundances with regard to WC properties in M 31.…”
Section: Comparison With Wc Stars In the Galaxymentioning
confidence: 74%
“…A 60 M star on the main-sequence would have a mass-loss rate of typically ∼2−5 × 10 −6 M yr −1 (Puls et al 1996), hence during its H-burning lifetime (4 Myrs; from the Geneva models) it would have lost 8-20 M of its envelope through its stellar wind In order to compare this meaningfully with the abundance ratios we derive, we must have confidence in the absolute abundances derived in our methods. To date the evaluation of this has been difficult, as pointed out in Smartt et al (2001a and Paper I. These studies have concentrated on differential analyses and comparisons of the difference between stellar subgroups, rather than assuming validity of the absolute abundances.…”
Section: Discussion Of the Evolutionary Scenarios For Sher 25mentioning
confidence: 99%
“…These were HD 2905, HD 14956 and HD 13854, which have very similar H , δ, γ lines and Si /Si  line strength ratios as Sher 25. These stars have been observed with the single-order spectrograph ISIS on the WHT, and the spectra have a coverage of 3900-4735 Å covering the main diagnostic lines of interest (see Smartt et al 2001a where the details of the instrument setup is described). The S/N of these spectra are very high (in excess of 200) and the line profiles are well resolved, hence they make excellent comparison templates.…”
Section: Observational Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, for M 101 Kennicutt et al (2003) have recently found systematic differences up to a factor 3 between abundances derived from some empirical calibrations and those derived from the direct method, the latter being lower. Smartt et al (2001) and Trundle et al (2002) have shown that in the Local Group spiral galaxy M 31 oxygen abundances of B supergiant atmospheres are also systematically lower than those obtained by classical R 23 -O /H calibrations. However, Monteverde et al (2000) found very good agreement between B supergiant abundances (obtained in a similar way as in the aforementioned references) and the abundances derived from the T e method in the interstellar medium in M 33.…”
Section: Introductionmentioning
confidence: 95%